A Synergetic Effect of Molecular Weight and Fluorine in All‐Polymer Solar Cells with Enhanced Performance. (28th October 2016) - Chen, Shanshan; An, Yujin; Dutta, Gitish K.; Kim, Yiho; Zhang, Zhi‐Guo; Li, Yongfang; Yang, Changduk
Abstract : A synergetic effect of molecular weight ( M n ) and fluorine (F) on the performance of all‐polymer solar cells (all‐PSCs) is comprehensively investigated by tuning the M n of the acceptor polymer poly(( N, N′ ‐bis(2‐octyldodecyl)‐naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl)‐ alt ‐5, 5′‐(2, 2′‐bithiophene)) (P(NDI2OD‐T2)) and the F content of donor polymer poly(2, 3‐bis‐(3‐octyloxyphenyl)quinoxaline‐5, 8‐dyl‐ alt ‐thiophene‐2, 5‐diyl). Both M n and F variations strongly influence the charge transport properties and morphology of the blend films, which have a significant impact on the photovoltaic performance of all‐PSCs. In particular, the effectiveness of high M n in increasing power conversion efficiency (PCE) can be greatly improved by the devices based on optimum F content, reaching a PCE of 7.31% from the best all‐PSC combination. These findings enable us to further understand the working principles of all‐PSCs with a view on achieving even higher power conversion efficiency in the future. Abstract : To establish a correlation between the effects of molecular weight ( M n ) and fluorine (F) on photovoltaic performance, all‐polymer solar cells have been comprehensively investigated based on donor polymers of TQ family with various F content and P(NDI2OD‐T2) acceptor polymers with various M n . An efficiency of 7.31% is demonstrated by blending the optimum F content‐containing donor with a high M n acceptor.